Concentração letal 'CL IND.50-96H' e efeitos sub-letais do selenito de sódio ('NA IND.2'SE'O IND.3') em tilápia do nilo, Oreochromis niloticus (linnaeus, 1757): alterações hematológicas e histopatológicas - Gonçalves, Adriano [UNESP] (2004)
This work was a bioassay with tilapia, Oreochromis niloticus, performed in order to evaluate acute and chronic toxicity caused by sodium selenite. In order to determine Mean Lethal (CL50) concentration, acute toxicity test was used in juveniles submitted to different concentrations of selenito in the water. In the chronic toxicity test, four conditions were tested: a control one, two concentrations estimated from fractions CL50 / 10 (0.4 mgSe4+/L) and CL50 /100 (0.04 mgSe4+/L), and a last one, reported by CONAMA resolution (1986) (0.01 mgSe4+/L). The trial lasted 14 days, and sampling consisted of two individuals per treatment collected in the following intervals: 0, 3, 7, 10 and 14 days, in the evaluation of sublethal chronic effects. Samples were submitted to hematological and histopathological analyses. Hematological parameters analyzed were: erythrocyte count (Er), hemoglobin level (Hb), hematocrit (Ht), thrombocyte count (Tr), total and differential leukocyte count and calculation of absolute hematimetric indices: mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC). Fragments of branchia, liver and kidneys were collected and fixed and formaldehyde 10% for 24 hours at room temperature. They were then transferred to alcohol 70% and placed in jars to be later on included in paraffin. Six-μm thick sections were produced and stained using hematoxilin-eosin. According to the results obtained, it was possible to determine mean lethal concentration (CL50) for sodium selenite as equal to 4.29 mgSe4+/L, for tilapia juveniles. Hematological analyses showed that significant differences (p<0.05) could be observed in the following parameters: mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), mean corpuscular hemoglobin (MCH) and hemoglobin concentration (Hb), when selenite concentration was equal to ...